2014
DOI: 10.1242/jeb.097469
|View full text |Cite
|
Sign up to set email alerts
|

Amphibious hearing in spotted seals (Phoca largha): underwater audiograms, aerial audiograms and critical ratio measurements

Abstract: Spotted seals (Phoca largha) inhabit Arctic regions that are facing both rapid climate change and increasing industrialization. While little is known about their sensory capabilities, available knowledge suggests that spotted seals and other ice seals use sound to obtain information from the surrounding environment. To quantitatively assess their auditory capabilities, the hearing of two young spotted seals was tested using a psychophysical paradigm. Absolute detection thresholds for tonal sounds were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 51 publications
5
44
1
Order By: Relevance
“…The audiograms for the two subjects are in good agreement from 0.1 to 25.6 kHz, above which the adult male (Natchek) exhibits apparent high-frequency hearing loss. The thresholds of the young female (Nayak) are quite similar to those reported recently for harbor (Kastelein et al, 2009;Reichmuth et al, 2013) and spotted seals (Sills et al, 2014) across the hearing range. In contrast to historical data, these ringed seal audiograms are consistent with the hypothesis of a functional hearing group for northern seals.…”
Section: Discussion Underwater Hearingsupporting
confidence: 83%
See 4 more Smart Citations
“…The audiograms for the two subjects are in good agreement from 0.1 to 25.6 kHz, above which the adult male (Natchek) exhibits apparent high-frequency hearing loss. The thresholds of the young female (Nayak) are quite similar to those reported recently for harbor (Kastelein et al, 2009;Reichmuth et al, 2013) and spotted seals (Sills et al, 2014) across the hearing range. In contrast to historical data, these ringed seal audiograms are consistent with the hypothesis of a functional hearing group for northern seals.…”
Section: Discussion Underwater Hearingsupporting
confidence: 83%
“…Regardless, the in-air thresholds measured for these ringed seals are among the lowest reported for marine mammals. When compared with available data for ice-living seals, these ringed seal audiograms -along with recent data for spotted seals (Sills et al, 2014) -show significantly better sensitivity to airborne sounds than measured previously for one harp seal (Terhune and Ronald, 1971). While others have suggested that the harp seal thresholds were elevated as a result of noise (Watkins and Wartzok, 1985;Moore and Schusterman, 1987), the reported ambient noise levels and CRs (Terhune and Ronald, 1971) suggest that masking was not a relevant factor.…”
Section: In-air Hearingmentioning
confidence: 48%
See 3 more Smart Citations